Decentralised control strategy for hybrid battery energy storage system with considering dynamical state‐of‐charge regulation. Issue 6 (25th November 2020) - Zhang, Yan; Ji, Feng; Hu, Qi; Fu, Lijun; Gao, Xueping
Abstract : Hybrid battery energy storage system (HBESS) consists of high power density battery and high energy density battery will have a bright future in special isolated DC microgrid conditions such as the all‐electric ships and all‐electric airplanes, which have strict limitation on storage capacity and size. In this study, a new decentralised control strategy based on mixed droop is proposed to HBESSs with considering the batteries. In decentralised control strategy, conventional V – I droop controller is utilised to high energy density battery to mainly supply the steady power, I – V droop controller is utilised to high power density battery to respond to power change and supply a few steady power. In addition, dynamical state‐of‐charge (SoC) regulation algorithm is utilised to reassign the battery power according to their own SoC. The power coordination of the high energy density batteries and high discharge rate batteries is achieved by adjusting the values virtual impedance and reference input voltage. Case study shows that the proposed control strategy is flexible and efficient.